Analyzed the Physicochemical Characteristics, Zooplankton Fauna variety of betwa river (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Environmental physicochemical factors cause zooplankton populations to fluctuate, and water quality variables including temperature, light penetration, nutrient enrichment, herbivores, and heterotrophic bacteria all play a role in determining zooplankton density.  The presence of aroma, taste, turbidity, and visible particles in water may therefore be better comprehended by using plankton analysis values. Their contributions to the biological output of ecosystems are substantial, and they also play an essential role in the lentic community. Most zooplankton populations in freshwater habitats are made up of rotifers, cladocerans, and copepods.  Not only do these creatures provide a substantial amount of food for invertebrates and planktivorous fish, but they also play an important part in the energy transfer and nutrient cycling processes that occur within aquatic food webs.   There can be unexpected changes in population size in the event of a disturbance due to the complex interactions that these organisms maintain with their surroundings throughout their lifetimes.  Which is why changes in their population size, species diversity, or community composition could tell us a lot about  environmental health.